Interest in the development of integrated rural tourism activities in three communities of Sonora - Figueroa González, Luis Fernando; Cavazos Arroyo, Judith; Mayett Moreno, Yesica (Revista Mexicana de Ciencias Agrícolas, 2018)
Misuse of the commercialization of natural resources and tourism products undermines the credibility and authenticity of some proposals of rural tourist destinations. A recent approach known as integrated rural tourism (IRT) proposes the integration among the various ores act involved in this activity highlighting sustainability as a competitive advantage and the inclusion of local and regional economies. This research analysed the interest in getting involved in IRT activities by three actors in the social chain: people of the communities of Ures, Baviácora and Aconchi, potential tourists and tourism providers in Hermosillo, Sonora. A quantitative, descriptive, explanatory and multi-cross divided research was developed into three stages. The results highlight the willingness of community residents to take advantage of the resources of IRT and interest in the development of tourism activities in each destination. Most of the tourist service providers would be willing to invest jointly with members of the community, valuing projects that link the cultural heritage of natural resources. Meanwhile, potential tourists value resting, natural resources and rural experiences. The integration requires a reeducation of the actors in this social chain, regarding their perception of leisure and enjoyment of cultural and natural attractions.
Keywords: inclusion; Mexico; social integration; sustainability